1997
DOI: 10.1111/j.1600-0714.1997.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Single cell gel electrophoresis on peripheral blood leukocytes of patients with oral squamous cell carcinoma

Abstract: The single cell gel electrophoresis (SCGE) assay, also known as the comet assay, is a cytogenetic technique for measuring and analyzing DNA single stranded breaks (SSB) and/or alkali labile sites within individual cells. Peripheral blood leukocytes of 22 oral squamous cell carcinoma (OSCC) patients were subjected to SCGE and the DNA damage levels (SSB) were quantified with respect to clinical staging and histopathologic grading. Highly statistically significant differences in DNA damage levels were found betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
(4 reference statements)
1
20
0
Order By: Relevance
“…Nevertheless, endogenous cellular processes may induce DNA damage and serve as a source of genomic instability. Previous studies have showed DNA damage in blood cells of oral cancer patients assessed by the single cel gel (comet) assay (Rao et al 1997). The results support the concept of a systemic host response in malignancy.…”
Section: Discussionsupporting
confidence: 75%
“…Nevertheless, endogenous cellular processes may induce DNA damage and serve as a source of genomic instability. Previous studies have showed DNA damage in blood cells of oral cancer patients assessed by the single cel gel (comet) assay (Rao et al 1997). The results support the concept of a systemic host response in malignancy.…”
Section: Discussionsupporting
confidence: 75%
“…25 Using the same technique, the PBL of patients with OSCC, showed a significant increase in DNA damage, depending on the clinical staging and histopathological grading. 19 The DNA damage levels in PBL in patients with precancerous lesions of the cervix, showed a significant stepwise increase in the mean DNA damage in the leukocytes, from normal or control groups to patients with different grades of dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were then transferred in to glass bottles containing 3.8% sodium citrate. Single cell electrophoresis was carried out for both these groups and the DNA damage was quantified using a fluorescence microscope following the method outlined by Rao et al 19 and Singh et al 20 …”
Section: Collection Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations